Zur Morphologie und Biologie der Präimaginalstadien des Sitona-Parasiten Campogaster exigua (Meig.) (Diptera: Larvaevoridae). - Müller, Hubert (Contributions to Entomology = Beiträge zur Entomologie, 1962)
Descriptions are given of all immature stages (27 figures) of Campogaster exigua (Larvaevoridae). A comparison is made with the other known larvae of Dufouriini (parasites of Coleoptera) as well as with the known larvae of Phasiinae (parasitizing Heteroptera). The respiratory system of C. exigua and the other Dufouriini isamphipneustic in the 3rd larval stage, on the contrary the Phasiinae have a metapneustic system. C. exigua is also amphipneustic in the 2nd larval stage. From some points (Fig. 26) it is suggested, that the little sclerites in the ’Halsstück’-region (region of the hypostomal sclerite according to Lowne) of the larvae of Larvaevoridae and Calliphoridae correspond to one another. C. exigua was reared from adult Sitona humeralis, flavescens, lineatus, hispidulus, puncticollis, sulcifrons, and Phytonomus variabilis. The C. exigua larvae overwinter in the living host beetles. Due to the fact that C. exigua produces annual several generations unlike the hosts, which have only one generation a year, C. exigua must be regarded as a polyphagous parasite of Sitona.